The phosphoinositide 3-kinase signaling pathway in normal and malignant B cells: activation mechanisms, regulation and impact on cellular functions - Pauls, Samantha D.; Lafarge, Sandrine T.; Landego, Ivan; Zhang, Ting-ting; Marshall, Aaron J. (Frontiers in Immunology, 2012)
The phosphoinositide 3-kinase (PI3K) pathway is a central signal transduction axis controlling normal B cell homeostasis and activation in humoral immunity. The p110δ PI3K catalytic subunit has emerged as a critical mediator of multiple B cell functions. The activity of this pathway is regulated at multiple levels, with inositol phosphatases PTEN and SHIP both playing critical roles. When deregulated, the PI3K pathway can contribute to B cell malignancies and autoantibody production. This review summarizes current knowledge on key mechanisms that activate and regulate the PI3K pathway and influence normal B cell functional responses including the development of B cell subsets, antigen presentation, immunogloblulin isotype switch, germinal center responses and maintenance of B cell anergy. We also discuss PI3K pathway alterations reported in select B cell malignancies and highlight studies indicating the functional significance of this pathway in malignant B cell survival and growth within tissue microenvironments. Finally, we comment on early clinical trial results, which support PI3K inhibition as a promising treatment of chronic lymphocytic leukemia.